The Establishing of Adolescent Mental Health through Islamic Religious Education in the Family - Nisa ul Mukarromah; Ikhwan Aziz; Suhono Suhono; Haikal Haikal (International Journal on Advanced Science, Education, and Religion, 2024)
Mental health is a mental or psychological condition that shows a person's capacity to adapt and resolve challenges within themselves(internal) or problems that exist outside of him(external). Adolescence is a rapid physical, mental and intellectual growth and development and a phase of life in the future of this nation. so that teenagers are expected to have good mental health so they can express and develop. However, this phase is vulnerable to depressive symptoms so that deviant behavior occurs, especially at the age of 18-21 years when looking for work. This research aims to examine the formation of mental health in adolescent children through Islamic religious education in families in Gunung Baru Village, Gunung Labuhan District, Way Kanan Regency. This research is field research (field Research) which is qualitative. Which aims to find out the extent of Islamic religious education in Gunung Baru Village. Sources used primary and secondary data. Data collection using observation, interview and documentation. Based on the results of the analysis conducted by the researcher, the results concluded that the formation of adolescent mental health through Islamic religious education in the family is very good starting from teaching prayer, getting used to reading and listening to the Qur'an, dhikr and fasting as well as religious activities in Gunung Baru Village such as the activities of Risma (Masjid Islamic Youth) every Tuesday, Sholawat Berzanji every Friday night with the instruction of the religious elite in Gunung Baru Village and Karang Taruna as a social activity. Keywords: Mental Health, Adolescents, Islamic Religious Education